Efficiency of lipid accumulating Actinomycetes isolated from soil for biodiesel production: Comparative study with microalgae. Issue 9 (3rd May 2017) - El-Sheekh, Mostafa M.; Allam, Nanis G.; Shabana, Samia A.; Azab, Maha M.
ABSTRACT: Due to the global warming and the increase of toxic gases emitted from the fossil fuels and the increase of energy demand, it is necessary to look for alternative sources for biodiesel. In this work, fifty bacterial species were isolated from soil samples and the isolated bacteria were tested for their ability of lipid production. The most potent lipid producer was identified as Streptomyces coelicolor A3-NC:003888.3 using the 16S rDNA partial sequencing technique. The lipid production process was performed in a bench scale for pure S. coelicolor, Chlorella vulgaris (as a standard biodiesel producer) and mixed algal bacterial culture as a comparative study. The results indicated that 93% wt of fatty acids of Streptomyces was converted to the corresponding fatty acid methyl esters (biodiesel). After transesterification of the produced lipids, the obtained oil was characterized according to American Society for Testing and Materials (ASTM) standards. The density of bacterial biodiesel was 0.866 and that of algal biodiesel was 0.797; also the specific gravity was 0.866 and 0.784 for bacterial and algal biodiesel, respectively, giving more lubricant characters for bacterial biodiesel. The gross heating value of bacterial biodiesel (43426 Kj/Kg) was higher than that of algal biodiesel (41896 Kj/Kg), dependently, the cetane number of bacterial biodiesel (38) was little lower than that of algal biodiesel (43).